Sort by

- Relevance
- |Time

In mathematics,

**k**+**k**+**k**+**k**+**k**= 5k. => Let me explain this to you. There...**k**'s in the expression:**k**+**k**+**k**+**k**+**k**which**k**is common, then factor out**k**, i.e. (1 + 1 + 1 + 1 + 1)**k**= 5 ***k**= 5k. Or if you're familiar with this...4 Answers · Education & Reference · 01/11/2013

= (

**k**- 7)² =**k**(**k**) +**k**(- 7) - 7(**k**) - 7(- 7) = k² - 7k - 7k + 49 = k² - 14k + 49 Answer: k² - 14k + 495 Answers · Education & Reference · 26/02/2010

**k**= 0 is clearly a value for which the system has infinitely many solutions. Suppose**k**≠ 0. --**k**-**k**0**k**0 1 1-**k**0**k**-4**k**-1 3 -- 1 -1 0.... We still get no solutions if**k**= 1. Hence, we get infinite solutions if**k**...1 Answers · Education & Reference · 02/07/2013

**k**^2 + 2k - 15 = 0 This will factor easily. Q: what are two ...with a PRODUCT of -15, and a SUM of 2? A: 5 and -3 (**k**+ 5)(**k**- 3) = 0 One of the factors must equal zero. (i) If...4 Answers · Education & Reference · 22/10/2011

**k**- 5 1/8 = 9 3/10**k**- 41/8 = 93/10**k**= 93/10 + 41/8**k**= (93 * 4 + 41 * 5) / 40**k**= 577/40**k**= 14.4252 Answers · Education & Reference · 18/11/2014

**k**(x) = 6x^2 - 6x ---- I am assuming your problem is... 2....but if it is 6 times 2, then disregard this post.**k**(5) = 6(5^2) - 6(5)**k**(5) = 6(25) - 30**k**(5) = 150 - 30**k**(5) = 120**k**(-4) = 6(-4^2...3 Answers · Education & Reference · 10/05/2014

**k**/3 - 6 = 4 Add six onto both sides:**k**/3 = 10 Multiply each side by three:**k**= 30 And**k**= 30 is your answer.3 Answers · Education & Reference · 06/05/2009

5(

**k**+ 1) = 3k + 12; distribute the 5 5k + 5 = 3k + 12; subtract 3k from both sides 5k...5 - 5 = 12 - 5; simplify 2k = 7; divide each term by 2 2k/2 = 7/2; simplify & solve**k**= 7/2 <---------Answer Check: 5(7/2 + 1) = 3(7...5 Answers · Education & Reference · 15/04/2011

**k**/6 = 5/6 -2 since 2 = 12/6**k**/6 = (5-12)/6**k**/6 = -7/6 multiply both sides by 6**k**= -72 Answers · Education & Reference · 17/11/2012

Solving the first inequality gives you

**k**- 3 > 1 add 3 to both sides**k**- 3 + 3 > 1 + 3**k**> 4 ...that vertical line. We used a dotted or dashed line through**k**= 4 to indicate that that is not part of the solution. If we used...1 Answers · Education & Reference · 17/05/2008

##### Ad

related to**K**